KEBIJAKAN PENYELESAIAN KREDIT TIDAK EFEKTIF PADA KOPERASI DELTA KARYA JAYA - Aqillah Zahraani Huba (LPPM Universitas Bina Bangsa, 2023)
Savings and Loans Cooperative is one of the most widely used cooperatives in society today. Credit loans are one way that people use to manage and get additional business capital. Over time, business activities can suffer from poor results. This leads to irregularities and delays in loan repayments. This represents the risk of a cooperative credit loan. This loss is mainly due to the arrears of loans from the Delta Karya Jaya Savings and Loan Cooperative. The Cooperative has adopted several methods to deal with cases of arrears on loans. Namely, rescheduling, reconditioning, restructuring and amortization of loans. The purpose of this study is to clarify the policies implemented by the Savings and Loans Cooperative Delta Karya Jaya on the claim process and criteria for disbursing bad loans by the cooperative, and provide results. Depreciation requests that have not been made. The subject of the investigation is the profile and policy of handling claims of the Delta Karya Jaya Savings and Loans Cooperative. The method used consists of direct interviews with cooperative management, accounting and field staff, direct observation of the management of bad debts at the Delta Karya Jaya Savings and Loan Association, and collecting data from various sources. . The method used in this study is a qualitative descriptive method, which is a systematic, fact-based and precise discussion about one of the objects studied